2018
DOI: 10.1007/s11356-018-1973-7
|View full text |Cite
|
Sign up to set email alerts
|

BRC4Env, a network of Biological Resource Centres for research in environmental and agricultural sciences

Abstract: The Biological Resource Centre for the Environment BRC4Env is a network of Biological Resource Centres (BRCs) and collections whose leading objectives are to improve the visibility of genetic and biological resources maintained by its BRCs and collections and to facilitate their use by a large research community, from agriculture research to life sciences and environmental sciences. Its added value relies on sharing skills, harmonizing practices, triggering projects in comparative biology, and ultimately propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For this study, we selected all available strains of both collections identified as belonging to the genus Fragilaria and the closely related genus Ulnaria. For detailed information on the studied strains see Table S1 in the Supporting Information, and Rimet et al (2016), Kelly et al (2018), Mougin et al (2018), and Rimet et al (2018a).…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we selected all available strains of both collections identified as belonging to the genus Fragilaria and the closely related genus Ulnaria. For detailed information on the studied strains see Table S1 in the Supporting Information, and Rimet et al (2016), Kelly et al (2018), Mougin et al (2018), and Rimet et al (2018a).…”
Section: Methodsmentioning
confidence: 99%
“…Given the large size of NRPS genes and their numerous intragenic repeats, reflecting the repetitive cycle of reactions catalyzed by enzymatic modules, we used DNA chips to obtain a complete picture of the occurrence profiles of the odl -BGC genes and their linkage to the oatA gene in strains from our laboratory collection of Xenorhabdus and Photorhabdus (57 and 20 strains, respectively) ( 41 ). The Agilent oligonucleotide microarray used in this study carries two or three 60-mer probes per sequence of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Parasite material was maintained by the INRA animal parasite nematode collection 46 . Two H. contortus isolates with contrasted resistance status, i.e.…”
Section: Methodsmentioning
confidence: 99%